THE EFFECT OF VITAMIN C (L-ASCORBYL MONOPHOSPHATE-Mg) ON THE DEFORMITY PERFORMANCE OF HUMPBACK GROUPER (Cromileptes altivelis) LARVAE - Sophia Lasma Sagala; Suko Ismi; I Nyoman Adiasmara Giri (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
This study was aimed to get a standard protocol for vitamin C application in enrichment of Artemia nauplii and to examine the impact of vitamin C on humpback grouper larval deformity performance. Vitamin C in the form of L-ascorbyl-2-monophosphate-Mg (AMP-Mg) was used for the enrichment and incorporated into Artemia nauplii at a given level of 0-1.5 g/L with enrichment period of 4, 6, and 24 hours for each level. The effect of AMP on larval deformity was tested using the following treatments: unenriched both Artemia nauplii and commercial diet, un-enriched Artemia nauplii and experimental diet containing 2.5 g AMP-Mg/kg diet, enriched Artemia nauplii obtained from the protocol and commercial larval diet. Analysis of vitamin C content in Artemia nauplii was carried out using HPLC and larval deformities were observed using staining method, visual examination, or X-ray depending on larval age. The results showed that the best enrichment method of AMP in Artemia nauplii is achieved at the dose of 0.9 g/L for 6 h. The lowest percentage of abnormalities was found in larvae fed with enriched Artemia nauplii and commercial diets, suggesting that vitamin C has an important role in controlling larval deformities.